ANALISIS KEBIJAKAN KEPEMILIKAN HAK ATAS TANAH TUMPANG TINDIH DALAM PERSPEKTIF PERATURAN PEMERINTAH NO. 24 TAHUN 1997 - Muhammad Guntur (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2024)
This study aims to analyze the overlapping land rights ownership policy in the perspective of Government Regulation No. 24 of 1997 concerning Land Registration. Overlapping land rights is a problem that is often faced in land practice in Indonesia, which can lead to disputes between parties who have claims to the same piece of land. This study examines the role of land registration as one of the instruments regulated in the Government Regulation to provide legal certainty, as well as identify the obstacles faced in its implementation. The analysis was carried out by examining legal aspects related to land registration, land dispute resolution, and protection of the rights of landowners involved in overlapping cases.